Effects of Hypoxia on the Vestibular System in Obstructive Sleep Apnea Syndrome Observed on a Video Head Impulse Test - Fatih Topuz, Muhammet; Oğhan, Fatih; Akdağ, Gönül; Yıldız Gülhan, Pınar; Erdoğan, Onur; Arık, Özlem; Ceyhan, Aykut; Türe, Nurullah; Güvey, Ali (ENT Updates, 2021)
Objective: The aim of this research was to investigate the effects of hypoxia, observed in patients with obstructive sleep apnea (OSA) syndrome, on vestibular functions through the application of video head impulse test (v-HIT). Methods: Patients with sleep apnea/snoring complaints and who had undergone polysomnography (PSG) between January 10, 2019, and January 10, 2020, received a full otorhinolaryngological examination and v-HIT in this prospective cohort study. Polysomnography findings of 83 patients with appropriate criteria for the study (age, sex, body mass index (BMI), apnea-hypopnea index (AHI), and mean oxygen saturation) and v-HIT findings were compared. Results: Patients included in the study were divided into 4 groups according to the AHI scores. When age, gender, BMI, AHI, and mean oxygen saturation data were examined, only AHI scores showed statistically significant differences (P = .000). There was no statistically significant difference present between the groups in terms of mean vestibulo-ocular reflex (VOR) gains, mean asymmetry, overt and covert saccades in the right ear, and overt saccades in the left ear. There was a statistically significant difference between the groups in the covert saccade in the left ear (P = .014). Of all patients included in the study, 72 patients (86.5%) had pathological VOR gains and/or at least 1 overt/covert saccade. Conclusion: Our study with v-HIT concluded that the vestibular system is affected just as other systems in patients diagnosed with OSA syndrome. The literature review has proved that similar results were achieved in studies evaluating the vestibular system.